Penerapan PSAK No. 102 di BMT UGT Nusantara Cabang Pamekasan - Ira Farlizanty Tri Rahadi; Fadllan (Institut Agama Islam Negeri (IAIN) Madura, 2024)
PSAK No. 102 covers recognition and measurement, presentation and disclosure in murabahah financing in Sharia Cooperatives and Sharia Financial Institutions to sell or buy, as well as the implementation of murabahah transactions for cooperatives or Sharia financial institutions. Until now, many people are interested in murabaha financing. The number of enthusiasts who use murabaha financing, then automatically in murabaha financing will often be recorded transactions. The purpose of this study is to determine how the application of PSAK 102 at BMT UGT Nusantara Pamekasan Branch. By using qualitative methods with a case study approach and type of field research. Sources of data obtained through primary data and secondary data, which primary data to the deputy branch head, AOAP and teller, as well as secondary data in the form of financial reports from BMT UGT Nusantara Pamekasan Regency Branch. Based on the results of his research, in BMT UGT Nusantara Pamekasan Branch is in accordance with PSAK 102, but there are some points that are not yet appropriate and still need to be refined by BMT. Such as BMT does not provide murabahah without orders, BMT does not provide collateral other than motorcycle BPKB, BMT does not measure inventory at cost, BMT does not have significant risks associated with inventory ownership and BMT does not provide penalties.